The Relationship Between Uric Acid/HDL Ratio and Monocyte/HDL Ratio and Glycemic Control in Male Type 2 Diabetic Patients - Semra Özkan Öztürk; Seval Müzeyyen Ecin (Genel Tıp Dergisi)
Background: Type 2 diabetes mellitus (T2DM) is a major health problem worldwide. As glycemic control worsens, the risk of both microvascular and macrovascular complications increases. . The aim of this study was to investigate the relationship between blood glucose regulation and two different parameters: uric acid/HDL ratio (UHR) and monocyte/HDL ratio (MHR) in male subjects with type 2 diabetes. Methods: In this retrospective study, a total of 166 male patients diagnosed with type 2 diabetes and 83 healthy adult men as a control cohort were included. Diabetic male participants were equally divided into two subgroups: the group with uncontrolled blood glucose (HbA1c levels exceeding 7, n=83) and the group with good glycemic control (HbA1c levels at or below 7, n=83). Our analysis included assessment of several serum markers, including triglyceride, high-density lipoprotein (HDL), uric acid, low-density lipoprotein (LDL), neutrophil, lymphocyte, monocyte, white blood cell, hemoglobin and platelet levels. In addition, uric acid/HDL ratio, body mass index and monocyte/HDL ratio were compared. Results: Creatinine levels were normal in all study participants and ages were similar in the groups. Triglyceride levels were significantly higher in diabetic patients compared to the healthy group (P